Basis of contract clause: Balance between law and ethics - Mahdzir, Nazli (2009)
Section 151 of Insurance Act 1996 is enacted among other to resolve the issue of information obtained by agent while filling in proposal from on behalf of the insured.This issue is of great consequence since failure of the proposer to disclose material fact in the proposal form would enable the insurer to avoid the policy all together.However, the current trend or practices of insurer in inserting the basis of contract clause at the end of proposal forms has made the application of Section 151 with regard to insured duty of disclosure obsolete.This clause converts all the answers in the proposal form into warranties.All questions poses in the proposal form automatically become material facts even though some may in actual fact be immaterial.The effect of such clause is twofold.On one hand it helps to eliminate the necessity of considering whether such information is material or not, and whether there is disclosure of that material facts.On the other hand, the clause also seems to remove the responsibility of the insurer or agent to make sure that all material information had been obtained and recorded properly.By virtue of this clause, even if the proposer (insured) provides correct information but the insurer or agent mistakenly, negligently or purposely writes something else in the proposal form, the insurer is entitled to avoid the policy on the ground of non disclosure of material facts.This article explores the co-relations between law, ethics and practice in the insurance industry since the doctrine of ubberimae fidei set a contract of insurance apart from other types of commercial contracts.Thus, although it is a profit motivated industry, the insurer should not have a carte-blanche authority to include unfair terms which may result in the insured being denied compensation.